Analysis of Sidampak Service Innovation as Glocalization of E-government In Wukirsari Village, Sleman Regency - Hanantyo Sri Nugroho (ARISTO, 2020)
The Population Data Utilization System (Sidampak) in Wukirsari Village, Sleman Regency is a population administration service program that has provided many benefits. The background lacks clear planning in developing services to the community and a low level of community participation in the administration of population documents which then becomes the basis for creating a population administration service system that can provide complete, accurate, fast, easy and integrated results. This then led to a commitment for the village government of Wukirsari in making public service innovations. This innovation is not only the value of fast, easy, inexpensive, but more on the value of services that can be adapted to the culture of the Wukirsari community. Related, this study found that there are public services that consist of the Population Data Utilization System (Sidampak) program in Wukirsari Village which can then change service policies to better suit the social conditions of the community. Meanwhile, the research method used by researchers is a qualitative descriptive research method